2020
DOI: 10.1002/marc.201900660
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Step Solvent‐Free Synthesis of Poly(hydroxybutyrate)‐Based Photocurable Resin with Potential Application in Stereolithography

Abstract: A bio‐based polymeric ink for stereolithography developed through a two‐step solvent‐free process is herein proposed. Specifically, low‐molecular‐weight poly(hydroxybutyrate) (PHB)‐diol oligomers are prepared via molten transesterification of bacterial PHB with 1,4‐butanediol. Transesterification conditions such as diol concentration, catalyst amount, and reaction time are studied for optimizing the final oligomers’ molecular weight and structural features. In the second step, the oligomeric hydroxyl terminals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The peaks at 12.03 and 5.39 ppm indicate the presence of both carboxylic acid and alcoholic end groups, respectively, and the peaks in the 5 to 6 ppm region confirm the presence of both the allyl and cyclohexene functional groups within the polymer chain after polymerization (Supporting Information Figures 1−8), which could be leveraged for further reactions. As a representative case, 13 C NMR of poly(CyHene-co-AGE) (Supporting Information Figure 2) revealed peaks at 175.9, 175.5, and 174.6 ppm, indicating carboxylic acid end groups and ester linkages, as well as less-than-ideal selectivity in the polyester formation, an expected result when using stannous octoate as the catalyst. 56 AGE was polymerized into polyether derivative PEther(AGE) as reported elsewhere, and attempts to produce functionalized epoxide resulted in spontaneous ROPs at room temperature during photoirradiation and were therefore not explored further.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The peaks at 12.03 and 5.39 ppm indicate the presence of both carboxylic acid and alcoholic end groups, respectively, and the peaks in the 5 to 6 ppm region confirm the presence of both the allyl and cyclohexene functional groups within the polymer chain after polymerization (Supporting Information Figures 1−8), which could be leveraged for further reactions. As a representative case, 13 C NMR of poly(CyHene-co-AGE) (Supporting Information Figure 2) revealed peaks at 175.9, 175.5, and 174.6 ppm, indicating carboxylic acid end groups and ester linkages, as well as less-than-ideal selectivity in the polyester formation, an expected result when using stannous octoate as the catalyst. 56 AGE was polymerized into polyether derivative PEther(AGE) as reported elsewhere, and attempts to produce functionalized epoxide resulted in spontaneous ROPs at room temperature during photoirradiation and were therefore not explored further.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Considering the narrow temperature range (approx. 20°C) where PHB can be processed without thermal degradation, 68 the observed decreases of T g and T m are remarkable results…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 87%
“…Finally, PHB oligomers with methacrylate functionalities were obtained. This work showed that the developed methacrylated PHB oligomers were soluble in propylene carbonate at 90°C and after addition of photo-initiator were photo-polymerizable under UV light within 10 minutes (29).…”
Section: Polyhydroxyalkanoates Processed By Stereoli-polyhydroxyalkanoates Processed By Stereolithography Thographymentioning
confidence: 86%
“…(28). As crucial factors for the unproblematic SL process are considered the effective content of photo-sensible active terminating functional groups and the viscosity lower than 5 Pa.s (29). The typical stereolithographic prepolymers are acrylate monomers, methacrylate monomers, epoxides and vinyl ethers.…”
Section: Polyhydroxyalkanoates Processed By Stereoli-polyhydroxyalkanoates Processed By Stereolithography Thographymentioning
confidence: 99%